Neurochemistry, connectivity and plasticity of small intensely fluorescent (SIF) cells in the rat superior cervical ganglion - Heym, Christine; Common, Bernd; Yin, Shui; Klimaschewski, Lars Peter; Couraud, Jean-Yves; Bachmann, Sebastian (Annals of anatomy, 1993)
Applying double-labelling immunofluorescence, the peptide content of solitary and clustered small intensely fluorescent (SIF) cells, identified by an antiserum to a selective membrane glycoprotein marker, synaptophysin, was correlated with the presence of catecholamines in the rat superior cervical ganglion. Most of synaptophysin-immunoreactive solitary and clustered SIF cells apparently contained dopami-ne (indicated by tyrosine hydroxylase — TH) but not norad-renaline (indicated by dopamine-β-hydroxylase-DBH). Frequently, immunoreactivities for substance P or rarely, neuropeptide Y were colocalized in TH-immunolabelled cells of both types. Immunostaining for vasoactive intestinal polypeptide was found only in solitary SIF cells and was visible in TH-immunoreactive, as well as in TH-nonreactive cells. Very few solitary SIF cells were TH- and DBH-immu-noreactive. Solitary and clustered SIF cells, as a rule, were encircled by leu-enkephalin-positive fibres which were also met-enkephalin-arg6-phe7-immunoreactive, indicating proenkephalin as precursor. SIF cells were additionally approached by varicose fibres which contained immunoreactivity for calcitonin gene-related peptide (CGRP) but not for enkephalins. As observed by immuno-electronmicroscopy, fibres that were immunostained for leu-enkephalin or CGRP, deeply invaginated into SIF cell somata. In addition to close membrane appositions, CGRP-immunolabelled fibres exhibited efferent synaptic contacts wih elements of SIF cell clusters. SIF cells were non-reactive to enkephalin-antisera in control ganglia and after transection of the postganglionic nerves (axotomy); but both types exhibited leu-enkephalin in pre-ganglionically transected ganglia (decentralization) in which enkephalin-immunoreactive fibre baskets were absent. Synthesis of enkephalin in SIF cells after decentralization was confirmed by in situ hybridization demonstrating intracyto-plasmic proenkephalin messenger-RNA. The findings are indicative for a differential neurochemical equipment of SIF cells in the rat superior cervical ganglion, which mainly is independent to a topographical classification. Moreover, they demonstrate the involvement of two neuropeptides in preganglionic SIF cell innervation. Finally, the observations indicate the capacity of SIF cells for proen-kephalin-expression in response to preganglionic denervati-on.
Elektronische Reproduktion der Druck-Ausgabe 1. November 2011
Gesehen am 30.11.2023